The Aby Warburg’s Fundamental Concept Revised - Vicelja, Marina (IKON, 2014)
Abstract Barbara Baert, Nymph. Motif, Phantom, Affect. A Contribution to the Study of Aby Warburg (1866-1929), Studies in Iconology, 1, Leuven-Paris-Walpole, MA, 2014